THE IMPORTANCE OF TEACHING BIOPHYSICS WITH THE USE OF INTERACTIVE METHODS IN MEDICAL EDUCATION - Z.M.Narzullayeva (TADQIQOTLAR, 2025)
Abstract. This article analyzes the role of biophysics in medical education, its practical significance, its role in forming the competencies necessary for future doctors, and the main directions of biophysical research methods in modern medicine and interdependence of the various processes occurring in the human body, it is often possible to distinguish among them those that are close to physical processes. For example, such complex physiological processes as blood circulation are actually physical processes, since this process is associated with the flow of fluid - hydrodynamics, the propagation of elastic vibrations along the vessel - vibrations and waves, the mechanical work of the heart - mechanics, the generation of biopotentials - electricity, etc. Breathing is associated with the movement of gases - aerodynamics, heat transfer - thermodynamics, evaporation (spatial transitions), etc. C